Plan de negocios para la creación de una empresa dedicada a la comercialización de manjar de chontaduro (2013)
The present summary is entitled (TITULO) *business plan for the creation of a company dedicated to marketing of delicacy of Chontaduro, in the city of Santiago de Cali, in which the authors, Yuri Andrea Gutierrez, Maria Carolina Martinez Lopez and Diana Isabel Rueda Borrero ** presented the proposal for marketing a candy that blend traditional flavors of our pacific region, how is the Chontaduro and Manjar Blanco (milk candy) analyzing different and necessary aspects which lead to the achievement of the objectives. The document is structured by phases; begin with the type of information that the researchers adopted to make the job, the sources of information to consult. Followed by the different studies which allowed identify relevant aspects inside the market and determine what technical resources, administrative, financial are necessary for the realization of this project. To determine the consumption habits of the population of Cali, respect to Manjar Blanco and Chontaduro, a research of the markets was performed, using as technique of collecting the poll, this was applied to representative sample of potential consumers, the same way were analyze the strength and weaknesses of competitors and developing marketing plan. In the administrative study, legal a social, was achieved to determine what are the range and limitations that would have the project and the policy required for the company in accordance with standards established by the national government to operate. The financial and economic studies allows that it is possible to visualize the attainment of economic resources to fund this initiative, Further analysis showed that it is feasible and profitable its realization. In conclusion we demonstrated the sensitivity of the project linked to the increase or decrease in sales and in particular the quantities sold.